2014
DOI: 10.4103/0972-0707.124085
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization potential of bioactive glass and casein phosphopeptide-amorphous calcium phosphate on initial carious lesion: An in-vitro pH-cycling study

Abstract: Aims:The aim of this study was to evaluate and compare the remineralization potential of bioactive-Glass (BAG) (Novamin®/Calcium-sodium-phosphosilicate) and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) containing dentifrice.Materials and Methods:A total of 30 sound human premolars were decoronated, coated with nail varnish except for a 4 mm × 4 mm window on the buccal surface of crown and were randomly divided in two groups (n = 15). Group A — BAG dentifrice and Group B — CPP-ACP dentifrice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 18 publications
6
51
1
9
Order By: Relevance
“…Some previous studies have shown that the treatment of demineralized enamel by Asp-Ser-Ser (Chung and Huang, 2013;Chung and Li, 2013a,b;Yang et al, 2014) or amelogenin (Fan et al, 2011) promotes enamel remineralization. Moreover, the ability of casein phosphopeptides to improve enamel remineralization is well proven (Reynolds, '97;Mehta et al, 2014;Zhou et al, 2014). Proteins can bind to crystal faces to accelerate or inhibit crystal growth (Shiraga et al,'92).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have shown that the treatment of demineralized enamel by Asp-Ser-Ser (Chung and Huang, 2013;Chung and Li, 2013a,b;Yang et al, 2014) or amelogenin (Fan et al, 2011) promotes enamel remineralization. Moreover, the ability of casein phosphopeptides to improve enamel remineralization is well proven (Reynolds, '97;Mehta et al, 2014;Zhou et al, 2014). Proteins can bind to crystal faces to accelerate or inhibit crystal growth (Shiraga et al,'92).…”
Section: Discussionmentioning
confidence: 99%
“…CPP-ACP has remineralizing effect on artificial subsurface enamel lesions and the remineralization effect increased with increase in the usage of the paste on 1st, 5th and 10th day respectively [17]. There are studies comparing the enamel remineralization potential of CPP-ACP and BAG [18] and it was clearly shown that samples of both the groups had plugs that sealed the fissures formed by demineralization and hence it was concluded that both BAG and CPP-ACP were capable of remineralizing early carious lesion and BAG had the potential to remineralize to a greater extent when compared to CPP-ACP. In another study it was considered that both the materials are effective in repair and prevention of demineralization and BAG showed better results initially, but eventually both had similar remineralizing potential [19].…”
Section: Discussionmentioning
confidence: 99%
“…[13] The samples were then washed under deionized water, stored in artificial saliva for 10 days ( first cycle of remineralization) after which the samples were tested for microhardness and the values were recorded. Following this, ACP-CPP and BAG were applied for another 5 days and at the end of 15 days (second cycle of remineralization), the samples were subjected for microhardness testing using the same procedure as described earlier.…”
Section: Amorphous Calcium Phosphate-casein Phosphopeptide and Bioactmentioning
confidence: 99%